An overview of R&D in narrow-vein mining at Université Laval - C. Bourgoin (Canadian Institute of Mining, Metallurgy and Petroleum, 1994)
"The limited development and application of new technologies to narrow-vein mining is currently impeding progress in the industry to a point where productivity, working conditions and operating costs have reached a critical stage in many Canadian mines.In an effort to foster the emergence and application of new technologies, Université Laval, together with other organizations, has carried out a R&D project focussed on the need of identifying new development pos5ibilities and of facilitating the transfer of technology in matters related to underground mining methods and machinery.The first phase of the study consisted of an in-depth assessment of current practices and problems in narrow-vein mining. The second phase was a state-of-the-art survey of mining methods and equipment, together with proposed modifications and innovations. The third phase of the project concerns the experimental development as well as the principal application of various proposed technologies.This paper presents an overview of the organizational, technical and strategic considerations which guided the University group and it serves as well to introduce a newly-published brochure, entitled ""Underground Mining Techniques of Vein Deposits"", which summarizes such work to date. More specifically, a perspective of technological developments applicable to narrow-vein mining is presented."